2021
DOI: 10.1177/10497323211014844
|View full text |Cite
|
Sign up to set email alerts
|

The Experts’ Advice: Prevention and Responsibility in German Media and Scientific Discourses on Dementia

Abstract: In the absence of effective pharmacological therapy options, the focus of dementia and Alzheimer’s research has shifted from treatment and care to risk prediction, early detection, and prevention. Public health communication and media coverage regarding dementia emphasize the individual responsibility for dementia risk management. Focusing on the social and moral implications of the new understanding and public representation of dementia, we present an analysis of medical science, nursing science, and media di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Respective efforts might in turn foster acceptance of early diagnosis of the condition. On the other hand, recent studies have identified a shift in public and medical discourses about dementia, with strong focus on individual means of risk modification, running the risk of shifting responsibility for the condition one-sidedly on the individuals affected [18,19]. Over-emphasizing the potential of prevention might lead to increased fear or shame in older adults if they experience signs of cognitive decline, possibly making them more reluctant to be examined for an early diagnosis of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Respective efforts might in turn foster acceptance of early diagnosis of the condition. On the other hand, recent studies have identified a shift in public and medical discourses about dementia, with strong focus on individual means of risk modification, running the risk of shifting responsibility for the condition one-sidedly on the individuals affected [18,19]. Over-emphasizing the potential of prevention might lead to increased fear or shame in older adults if they experience signs of cognitive decline, possibly making them more reluctant to be examined for an early diagnosis of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…We derived 30 latent topics related to dementia from the posts by evaluating the 983,039 dementia-related Weibo posts and reviewing prior research on social media discussions of dementia [42][43][44][45][46]. Table 2 provides the 30 topics and top 10 unique keywords for each topic (a native Chinese-speaking researcher translated the words into English).…”
Section: Dementia Topics and Themesmentioning
confidence: 99%
“…The rise of social media and “digital health” has created new channels through which to propagate and enact responsibility discourses and practices (Erikainen et al, 2019 ; Lupton, 2016 , 2017 ; Rich & Miah, 2017 ). In parallel, scientific advances in neurology have stimulated “successful aging” discourses holding individuals personally responsible to prevent dementia by adopting a healthy lifestyle (Petersen & Schicktanz, 2021 ).…”
Section: Responsibility and Blamementioning
confidence: 99%
“…For example, Ryan ([ 1971 ] 1976 ), Wright ( 1993 ), and Greenbaum ( 2015 ) attacked earlier reliance on theories such as the culture of poverty for highlighting individual, rather than structural, failings. Similarly, social science health researchers such as Crawford ( 1979 , 2006 ), Mechanic ( 1993 ), Blaxter ( 1995 ), Finerman & Bennett ( 1995 ), Petersen & Lupton ([ 1996 ] 2000 ), Galvin ( 2002 ), Filc ( 2004 , 2005 ), Herrick ( 2009 ), Ayo ( 2012 ), Brown & Baker ( 2012 ), Baum & Fisher ( 2014 ), Ravn et al ( 2016 ), Hutchison & Holdsworth ( 2021 ), and Petersen & Schicktanz ( 2021 ) criticized the responsibility discourse as blaming the victim while ignoring societal and governmental responsibility for inequities, the failure to curb corporations' damage to the environment and marketing of unhealthy foods, etc. Bauman ( 2002 ) made a similar point about both unemployment and illness (p. xvi).…”
Section: Responsibility: Our Perspective…and Our Subjects’mentioning
confidence: 99%
See 1 more Smart Citation